What limits evaporation from Mediterranean oak woodlands – The supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? - Baldocchi, Dennis D.; Xu, Liukang (Advances in Water Resources, 2007)
The prediction of evaporation from Mediterranean woodland ecosystems is complicated by an array of climate, soil and plant factors. To provide a mechanistic and process-oriented understanding, we evaluate theoretical and experimental information on water loss of Mediterranean oaks at three scales, the leaf, tree and woodland. We use this knowledge to address: what limits evaporation from Mediterranean oak woodlands – the supply of moisture in the soil, physiological control by plants or the demand by the atmosphere? The Mediterranean climate is highly seasonal with wet winters and hot, dry summers. Consequently, available sunlight is in surplus, causing potential evaporation to far exceed available rainfall on an annual basis. Because the amount of precipitation to support woody plants is marginal, Mediterranean oaks must meet their limited water supply by a variety of means. They do so by: (1) constraining the leaf area index of the landscape by establishing a canopy with widely spaced trees; (2) reducing the size of individual leaves; (3) by adopting physiological characteristics that meter the use of water (e.g. regulating stomatal, leaf nitrogen/photosynthetic capacity and/or hydraulic conductance); (4), by tapping deep supplies of water in the soil; (5) and/or by adopting a deciduous life form, which reduces the time interval that the vegetation transpires.
Keywords: ecohydrology; evaporation; quercus douglasii; savanna; Transpiration

How plant functional-type, weather, seasonal drought, and soil physical properties alter water and energy fluxes of an oak–grass savanna and an annual grassland - Baldocchi, Dennis D.; Xu, Liukang; Kiang, Nancy (Agricultural and Forest Meteorology, 2004)
Savannas and open grasslands often co-exist in semi-arid regions. Questions that remain unanswered and are of interest to biometeorologists include: how do these contrasting landscapes affect the exchanges of energy on seasonal and annual time scales; and, do biophysical constraints imposed by water supply and water demand affect whether the land is occupied by open grasslands or savanna? To address these questions, and others, we examine how a number of abiotic, biotic and edaphic factors modulate water and energy ﬂux densities over an oak–grass savanna and an annual grassland that coexist in the same climate but on soils with different hydraulic properties. The net radiation balance was greater over the oak woodland than the grassland, despite the fact that both canopies received similar sums of incoming short and long wave radiation. The lower albedo and lower radiative surface temperature of the transpiring woodland caused it to intercept and retain more long and shortwave energy over the course of the year, and particularly during the summer dry period. The partitioning of available energy into sensible and latent heat exchanged over the two canopies differed markedly. The annual sum of sensible heat exchange over the woodland was 40% greater than that over the grassland (2.05 GJ m−2 per year versus 1.46 GJ m−2 per year). With regards to evaporation, the oak woodland evaporated about 380 mm of water per year and the grassland evaporated about 300 mm per year. Differences in available energy, canopy roughness, the timing of physiological functioning, water holding capacity of the soil and rooting depth of the vegetation explained the observed differences in sensible and latent heat exchange of the contrasting vegetation surfaces. The response of canopy evaporation to diminishing soil moisture was quantiﬁed by comparing normalized evaporation rates (in terms of equilibrium evaporation) with soil water potential and volumetric water content measurements. When soil moisture was ample normalized values of latent heat ﬂux density were greater for the grassland (1.1–1.2) than for the oak savanna (0.7–0.8) and independent of moisture content. Normalized rates of evaporation over the grassland declined as volumetric water content dropped below 0.15 m3 m−3 , which corresponded with a soil water potential of −1.5 MPa. The grassland senesced and quit transpiring when the volumetric water content of the soil dropped below −2.0 MPa. The oak trees, on the other hand, were able to transpire, albeit at low rates, under very dry soil conditions (soil water potentials below −4.0 MPa). The trees were able to endure such low water potentials and maintain basal levels of metabolism because ecological forcings kept the tree density and leaf area index of the woodland low, physiological factors forced the stomata to close progressively and the trees were able to tap deeper water sources (below 0.6 m) than the grasses.
Keywords: Biosphere–atmosphere interactions; ecohydrology; evaporation